PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN PUZZLE GAMBAR TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN MATEMATIKA SISWA KELAS V DI SDN GANDEKAN SURAKARTA - Fadhila Syahida; Feri Faila Sufa; Mukhlis Mustofa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was conducted at SDN Gandekan Surakarta. The subjects of this research were Grade V with 18 students. This research used quantitative research. The sampling and instrument testing were carried out with validity and reliability tests. The technique in data collection used prerequisite tests with the Shapiro-Wilk formula as an initial stage test and the hypothesis test used a paired sample t-test. After data analysis and discussion, it can be concluded that there is a difference in the critical thinking skills of grade V before treatment and after treatment when applying picture puzzle learning media at SDN Gandekan. In the pretest activity, the mean was 47.22, the minimum value was 20 and the maximum was 80, while after treatment the mean was 68.33, the minimum value was 50 and the maximum value was 90. The results of data analysis for the paired sample t-test showed that there was a difference between the variables at the beginning and the variables at the end of the pretest and posttest. Paired Simple T-Test shows that Ho is rejected and Ha is accepted because the significance value (2-tailed) is 0.001 < 0.05 which proves that there is an influence of the use of picture puzzle learning media on critical thinking skills in mathematics subjects of grade V students at SDN Gandekan Surakarta.